Synthesis, Cytotoxicity, Xanthine Oxidase Inhibition, Antioxidant of New Pyrazolo{3,4 d}Pyrimidine Derivatives (Baghdad Science Journal, 2019)
Allopurinol derivative were prepared by reacting the (1-chloroacetyl)-2-Hydropyrazolo{3,4-d}pyrimidine-4-oneiwith 5- methoxy- 2-aminoibenzothiazoleiunder certain conditions to obtain new compound ( N- (2-aminoacetyl (5-methoxy) benzothiazole -2yl) (A4), Reaction of 5-(P-dimethyl amine benzene)-2-amino-1,3,4- oxadiazole in the presence of potassium carbonate anhydrous to yield new compound (N-(2- aminoacetyl-5-(P-dimethyl amine benzene )-1,3,4-oxadiazoles-2-yl)(A30) and Azo compound (N-(5-(Azo-2-hydroxy-5-amino benzene)-1,3-Diazol-2yl)Allopurinol(A46). The structure of prepared compounds were confirmed by (FT-IR) technique and their physical properties. The synthesized compounds were tested for cytotoxicity, Xanthine oxidase inhibition, and antioxidant activity.